2021
DOI: 10.1097/iae.0000000000003182
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and Choroidal Blood Perfusion in Patients With Bietti Crystalline Dystrophy

Abstract: Purpose: To compare changes of chorioretinal blood perfusion between Bietti crystalline dystrophy (BCD) and typical retinitis pigmentosa and perform a staging and a longitudinal analysis of chorioretinal perfusion in BCD.Methods: Twenty-eight patients with BCD (56 eyes), 28 patients with typical retinitis pigmentosa (56 eyes), and 28 healthy subjects (56 eyes) were enrolled. Macular structural parameters and subfoveal choroidal thickness were measured using optical coherence tomography. Retinal vessel and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Moreover, OCTA is a new way to monitor choroidal blood flow changes in BCD, revealing the decrease of choroidal blood flow and abnormal angiogenesis in the choroid [38] . In addition, Xu et al [39] reported that the deficit of choroidal perfusion impaired in BCD may be more pathologic than the deficit retinal blood perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OCTA is a new way to monitor choroidal blood flow changes in BCD, revealing the decrease of choroidal blood flow and abnormal angiogenesis in the choroid [38] . In addition, Xu et al [39] reported that the deficit of choroidal perfusion impaired in BCD may be more pathologic than the deficit retinal blood perfusion.…”
Section: Discussionmentioning
confidence: 99%